SIMPLE METHODS FOR ESTIMATION OF PARAMETERS FOR ASSESSING EXPLOITED FISH STOCKS - Alagaraja, K (Indian Journal of Fisheries, 2011)
New methtxls for estimation of growth and mortality parameters, together with their error estimations, are given, discussing in detail their advantages over the existing ones. A new model called Relative Response model has been designed for estimation of such stocks that are common in tropics where the application of other models are not effective. Demonstrative worksheets are provided to illustrate easy working of the methods. Various proformae for collection of data are appended.